Various CO2-to-CO Electrolyzer Cell and Operation Mode Designs to avoid CO2-Crossover from Cathode to Anode - Reinisch, David; Schmid, Bernhard; Martić, Nemanja; Krause, Ralf; Landes, Harald; Hanebuth, Marc; Mayrhofer, Karl; Schmid, Günter (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2019)
The electrochemical CO2 reduction reaction (CO2RR) towards CO allows to turn CO2 and renewable energy into feedstock for the chemical industry. Previously shown electrolyzers are capable of continuous operation for more than 1000 h at high faradaic efficiencies and industrially relevant current densities. However, the crossover of educt CO2 into the anode gas has not been investigated in current cell designs: Carbonates (HCO3 - and CO3 2-) are formed at the cathode during CO2RR and are subsequently neutralized at the anode. Thus, CO2 mixes into the anodically evolved O2, which is undesired from commercial perspectives. In this work this chemical transport was suppressed by using a carbonate-free electrolyte. However, a second transport mechanism via physically dissolved gases became apparent. A transport model based on chemical and physical absorption of CO2 and O2 will be proposed and two solutions were experimentally investigated: the use of an anode GDL (A-GDL) and degassing the anolyte with a membrane contactor (MC). Both solutions further reduce the CO2 crossover to the anode below 0.1 CO2 for each cathodically formed CO while still operating at industrially relevant current densities of 200 mA/cm2
CRIS-Team Scopus Importer:2019-12-20
Keywords: CO; CO; CO; CO; electrochemical CO generation; electrochemistry; high current density